THE SEMIOTICS OF PROPAGANDA SPEECH IN SOCIAL MEDIA SITES: A Semiotic Study of the News Reports on the Israeli "Makan" Channel - Saleh, Ali Al-Karar Muhammed; Al-Kinani, Muhsin Chalub; Mubarak, Muhammed Ridhah (ALBAHITH ALALAMI, 2021)
Technological and digital development has allowed the emergence of many methods of producing semantics on social media sites within semiotic and propagandistic frameworks. This is what made the image appear in different molds and shapes, especially as it is the first material for visual perception. This made the Israeli propaganda discourse use it as an important tool to manage the content of suggestive messages with semiological connotations. By doing so, such tool uses social networking sites as an appropriate environment to achieve those goals, which are related to cases of manipulating emotions and minds. It, moreover, changes convictions, attitudes, trends and behaviors according to what the propaganda planner wants. Many Israeli Websites compete in seeking to pass on ideas whose emotional and cognitive contexts are related to symbolic references in producing the semantic meaning of the propaganda discourse. Among the most important of these sites is the Israeli Makan Channel Website.